Readiness, recovery, and strain: an evaluation of composite health scores in consumer wearables - Doherty Cailbhe; Baldwin Maximus; Lambe Rory; Burke David; Altini Marco (Translational Exercise Biomedicine, 2025)
Consumer wearables increasingly provide users with Composite Health Scores (CHS) – integrated biometric indices that claim to quantify readiness, recovery, stress, or overall well-being. Despite their growing adoption, the validity, transparency, and physiological relevance of these scores remain unclear. This study systematically evaluates CHS from leading wearable manufacturers to assess their underlying methodologies, contributors, and scientific basis.